How Science Runs - Mittemeijer, Eric J. author. aut Link
XVI, 266 p. 28 illus., 14 illus. in color.
Keywords: This book offers a considered yet entertaining reflection on the progress of modern scientific research. The winding path of science can only be understood by revealing the personal, human side of scientific research, demystifying the actions of the scientist and exposing the human drama on the stage of science. The book looks at the true nature of contemporary science and scientists through the lens of the personal experiences of the author, a renowned and leading materials scientist, over the last half century. It examines the positive threads of modern scientific progress in sober juxtaposition to the manifest negative developments arising from stiff competition within the current academic landscape. A collection of stories and real-life anecdotes is presented in parallel to the career of the author, providing a first-hand account of important achievements in the field of materials science. As a result, this book provides fascinating reading for students, seasoned scientists, and anybody else interested in the workings and machinations of modern science.